Apokryficzny "Dialogus Iohannis cum Iesu" (CApNT 27) jako gnostycka reinterpretacja dziejów patriarchów i komentarz do Hbr 7, 3 - Zarzeczny, Rafał (Vox Patrum, 2007)
This article contains Polish translation and commentary to an apocryphal Gnostic text known as Dialogus Johannis cum Iesu (CApNT 27). The fragmental Coptic manuscript from the Deir el-Bala’izah collection (IV/V century A.D.) is the unique known testimony of this document. The text has a form of dialog between John the Apostle and the Risen Christ or some celestial messenger on creation and story of antediluvian patriarchs. Document reveals a particular similitude with other Gnostic texts, especially the Apocryphon of John from the Nag Hammadi library. It conserves the fragment of Hebr. 7:3, which probably received a large explanation in original document. The speculation on biblical personages, especially on Melchisedek, appears to be an important element in this text. The placement of Melchisedek’s name immediately after the name of Noah may suggests the identification of Melchisedek with Shem, the Noah’s son. Similar motif is known to us from the Jewish and ancient Christian literature, for instance the targumic elaborations of Genesis and the Syriac apocryphal text called Cave of Treasures (Spelunca thesaurorum).